The law of passing-off : unfair competition by misrepresentation - Wadlow, Christopher (Sweet & Maxwell LondonGB, 2004)
Includes information on the international law of unfair competition under the Paris Convention for the Protection of Industrial Property, with a detailed account of the drafting and negotiating history of Article 10bis of the latter. Looks at the possible impact of the European Convention of Human Rights, the WTO TRIPs Agreement and on unfair competition in private international law. Deals with the law of injurious falsehood principally as it applies between competitors, but drawing on cases between non-competitors where matters of principle are concerned.